The impact of allergic rhinitis in clinical practice: an Italian Survey - Passali, Desiderio; Bellussi, Luisa Maria; Damiani, Valerio; Passali, Francesco Maria; Motta, Gaetano; Ciprandi, Giorgio (Acta Biomedica Atenei Parmensis, 2020)
Allergic rhinitis (AR) is a very common disorder. The current Survey was conducted on a sample of about 5,000 adult subjects in 5 Italian cities. A questionnaire, containing 15 questions, was administered on the road. AR affects about 20% of the general population. The most common diagnostic test was the skin prick test, but only 12% of patients performed an allergy test to confirm the diagnosis. About 50% of patients did not take any medicine. Even about 40% of treatments were suggested by friends or pharmacists. In conclusion, the current Survey demonstrated that AR is a common disorder in Italy, the diagnostic work-up is still incorrect, and the therapeutic approach does not adhere to the guidelines. Therefore, there is a need to implement adequate information on this topic in Italy.